Campath-1G in vivo confers a low incidence of graft-versus-host disease associated with a high incidence of mixed chimaerism after bone marrow transplantation for severe aplastic anaemia using HLA-identical sibling donors. - Hamblin, M; Marsh, J; Lawler, M; McCann, SR; Wickham, N; Dunlop, L; Ball, S; Davies, E; Hale, G; Waldmann, H; Gordon-Smith, E (1996)
We have evaluated the effect of in vivo Campath-1G on engraftment and GVHD in 23 patients with severe aplastic anaemia transplanted from HLA-identical sibling donors. In 14 patients Campath 1g was given pre-transplant for up to 9 days in an attempt to overcome graft rejection (group 1). In nine patients Campath-1G was given pre-transplant, but also continued post-transplant until day +5 to reduce GVHD (group 2). There were three patients with late graft failure in group I following initial neutrophil engraftment, and four cases of grade II+ GVHD. In group II, two patients had early graft failure (no take), and there were no cases of acute GVHD out of seven evaluable patients. One patient in group I developed chronic GVHD of the liver, and two patients (one in each group) had transient localised chronic GVHD. PCR of short tandem repeats was used to evaluate chimaeric status in 13 patients. Of 11 patients with initial neutrophil engraftment, only one had 100% donor haemopoiesis at all times. The remaining patients had either transient mixed chimaerism or persistence of recipient (< 20%) cells. We conclude that in vivo Campath-1G is associated with a high incidence of mixed chimaerism which tips the balance away from GVHD but towards graft rejection.